A not-stop-flow online normal-/reversed-phase two-dimensional liquid chromatography–quadrupole time-of-flight mass spectrometry method for comprehensive lipid profiling of human plasma from atherosclerosis patients - Li, Min; Tong, Xunliang; Lv, Pu; Feng, Baosheng; Yang, Li; Wu, Zheng; Cui, Xinge; Bai, Yu; Huang, Yining; Liu, Huwei (Journal of Chromatography A, 2014)
•A not-stop-flow online NP/RP 2D LC-MS method was developed for lipid profiling.•Overall, 540 endogenous lipid species from 17 classes were identified from human plasma.•This novel method showed high sensitivity (ng/mL grade) and good repeatability.•Successful separation of isomers of GalC and GluC was achieved.•The levels of GalC and GluC were different in human plasma from different subjects. A not-stop-flow online two-dimensional (2D) liquid chromatography (LC) method was developed for comprehensive lipid profiling by coupling normal- and reversed-phase LC with quadrupole time-of-flight mass spectrometry (QToF-MS), which was then applied to separate and identify the lipid species in plasma, making its merits in quality and quantity of the detection of lipids. Total 540 endogenous lipid species from 17 classes were determined in human plasma, and the differences in lipid metabolism products in human plasma between atherosclerosis patients and control subjects were explored in detail. The limit of detections (LODs) of 19 validation standards could all reach ng/mL magnitude, and the RSDs of peak area and retention time ranged 0.4–8.0% and 0.010–0.47%, respectively. In addition, a pair of isomers, galactosylceramides (GalC) and glucosylceramides (GluC), was successfully separated, showing that only the levels of GalC in atherosclerosis patients were significantly increasing, rather than GluC, compared with the controls (controls vs. patients: the ratio was 1.5–2.8-fold increasing). It would be helpful to the further research of the atherosclerosis.